Exploring the prognostic value of HK3 and its association with immune infiltration in glioblastoma multiforme - Yang, Yuling; Fu, Xing; Liu, Runsha; Yan, Lijuan; Yang, Yiping (Frontiers in Genetics, 2023)
Background: Hexokinase 3 (HK3) is one of the key enzymes involved in glucose phosphorylation, which is the first step in most glucose metabolic pathways. Many studies have shown that HK3 was dysregulated and played vital roles in multiple tumors. However, the role of HK3 in glioblastoma multiforme (GBM) has yet to be studied in depth. Methods: All data were available from The Cancer Genome Atlas (TCGA) and Chinese Glioma Genome Atlas (CGGA). Kaplan-Meier and univariate regression were applied for survival analysis. Gene set enrichment analysis (GSEA) was used for enrichment analysis. The database of Tumor Immune Single Cell Hub (TISCH) was applied for single-cell analysis. Tumor Immune Dysfunction and Exclusion (TIDE) analysis was applied to evaluate the immune response. Result: The HK3 expression was up-regulated and correlated with poor prognosis in GBM. Enrichment analysis revealed that the high HK3 expression group was primarily enriched in adaptive immune response, chemokine signaling pathway, cytokine-cytokine receptor interaction, etc. The majority of immune cells and the enrichment of immune-related pathways were significantly higher in the high HK3 expression group. HK3 significantly correlated with most immune cells, especially macrophages (P<0.001, R=0.81). HK3 was predominantly expressed in macrophages in most types of cancer by the TISCH. HK3 was significantly correlated with most immune-related genes， such as PD-1 (P<0.001, R=0.41), PDL-1 (P<0.001, R=0.27), and CTLA-4 (P<0.001, R=0.29). TIDE analysis revealed that the low HK3 expression group has a lower TIDE score and may benefit from immunotherapy. Drug sensitivity analysis showed that patients with high HK3 expression were frequently associated with drug resistance. Conclusion: HK3 was significantly associated with poor prognosis and can be served as a biomarker of macrophages in GBM. HK3 was also associated with immune response and drug resistance. This helps to provide us with a new direction for GBM immunotherapy.